Floristic Composition of Restored Atlantic Riparian Forests on The Coast of São Paulo State, Brazil - Moschetto, Fernanda Augusto [UNESP]; Magenta, Mara Angelina Galvão; De Freitas, Débora Martins [UNESP] (FapUNIFESP (SciELO), 2022)
Studies on floristic composition are important to evaluate the effectiveness of forest restoration and to support conservation of tropical forests. Presence of planted exotic species and low species richness in several riparian forests in Brazil led us to analyze the floristic composition of restored riparian areas in a region with one of the highest levels of vegetation cover in the Atlantic Forest and immersed in one of the largest centers of endemism in this hotspot. Restored areas were identified through consultation of licensing processes at the environmental agencies and field visits were carried out in these areas to identify planted species. Most restorations involved the planting of exotic species, low species richness and an inadequate proportion of native species, which can be harmful to the conservation and restoration of the Atlantic Forest. Dissemination of these results may alert the environmental agencies in order to avoid the approval of ineffective restorations
Keywords: Biodiversity; Conservation; Endemism; Native vegetation; Planting of seedlings